Study of Assessment of Frequency, Indications and Complications of Peripartum Hysterectomy: An Institutional Based Study - Hitesh V. Bambhaniya (Asian Journal of Medical Research, 2018)
Background: Emergency peripartum hysterectomy (EPH) is a major surgical venture invariably performed in the setting of life-threatening haemorrhage during or immediately after abdominal and vaginal deliveries. This study was conducted to assess frequency, indications and complications of peripartum hysterectomy. Materials and Methods: This study was conducted to assess frequency, indications and complications of peripartum hysterectomy. There were 100 pregnant women who gave birth. The subjects had been explained about the procedure and were asked to give consent. All the subjects gave consent and had been included in the study. The frequency of peripartum hysterectomy had been assessed along with its indications and complications. The mean age of the subjects was 28.3 years. Statistical analysis had been conducted using SPSS software. Results: In this study, the prevalence of peripartum hysterectomy among who gave childbirth was 41%. Placenta accrete was evident in 15 cases and was the most common indication for peripartum hysterectomy. Other indications were atonic postpartum haemorrhage, rupture uterus and cervical pregnancy seen in 13,6 and 4 subjects, respectively. Post-abortal arteriovenous malformation was seen in 3 subjects. Urinary bladder injury was seen in 15 patients, adnexal bleeding was seen in 11 patients, retroperitoneal haematoma was seen in 10 patients. Blood transfusion was required in 12 patients. Coagulopathy was evident in 9 subjects, pulmonary oedema was seen in 10 cases, vaginal cuff cellulitis was seen in 5 cases and pneumonia was seen in 3 cases only. Conclusion: The frequency of peripartum hysterectomy in this study was 41%. The common indications for this procedure are placenta accrete, atomic postpartum haemorrhage, atonic postpartum haemorrhage, rupture uterus, cervical pregnancy and post-abortal arteriovenous malformation. The complications of this procedure were urinary bladder injury, adnexal bleeding, retroperitoneal haematoma, blood transfusion, coagulopathy, pulmonary oedema, vaginal cuff cellulitis and pneumonia.